The Tablighi Jamaat and its impact on Malaysian society - Butt, Daood Ahmed (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This research has been undertaken to examine the methodology of Da'wah used by the Tablighi Jamaat and to explore the Islamic influence and spread of the movement in contemporary Malaysia. To carry out this study, the researcher used data collected from books, journals, articles, newspapers, government reports and websites. Also, the researcher carried out interviews with five individuals, two of which are not members of the Tablighi Jamaat, while the other three are, and among them is the Amir of Tabligh for Malaysia. Fieldwork was conducted on numerous occasions at the Sri Petaling Markaz as well as various other Masaajid in Kuala Lumpur, Penang, Malacca and Johor Bahru. Towards this end, the researcher found that despite criticism around the world about the Tablighi Jamaat and weaknesses its members may possess in terms of Islamic knowledge, the initiative to carry the message of Islam is seen within them. In Malaysia, the cultural impact upon society is apparent and rich. This however does not conform with the practices of Tabligh, which is seen to be an opposing factor to the method of Islam practiced in the country. This research discovered from interviews that the differences between them can pose tensions within communities which at times seem to be harmless petty issues, yet could escalate into feeling a threat towards ones culture should a different practice of Islam be introduced. Members and leaders of the Tablighi Jamaat in Malaysia feel due to recent visits by political party leaders, including the Prime Minister, that they are achieving their mission one step at a time.